On Completeness of a System of Functions in an Angular Domain - Dilnyi, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We show that the system e −λz /(1 + z 2) : λ > 0 is complete in a class of functions analytic in an angle.